Analysis of Community-Based Nurses’ Preparedness in Flood Disaster Emergency Response - Pipin Yunus; Ani Retni (Journal La Medihealtico, 2025)
Flood disasters are one of the major threats in Gorontalo Province, with significant impacts on communities and the health service system. Nurses, as frontline health workers, play a strategic role in community-based emergency response, particularly in providing first aid, triage, and health education. This study aims to analyze the preparedness level of community-based nurses in responding to flood disasters in Limboto Barat District, Gorontalo Regency. A descriptive quantitative design with a cross-sectional approach was applied. The sample consisted of all 30 nurses working at Limboto Barat Public Health Center, selected through a total sampling technique. Data were collected using questionnaires and analyzed univariately. The results showed that most respondents were aged 31-40 years (36.7%), female (73.3%), had a bachelor’s degree in nursing (56.7%), and had more than five years of work experience (60%). Nurses’ preparedness was still low in terms of knowledge, with 73.3% categorized as poor. Regarding attitudes, 60% of respondents showed poor preparedness, while skills were mainly in the fair (46.7%) and poor (46.7%) categories. These findings indicate that community-based nurse preparedness is still not optimal, especially in the dimensions of knowledge, attitude, and skills. In conclusion, structured interventions through continuous training, disaster simulations, and cross-sectoral collaboration are required to strengthen nurses’ preparedness capacity in responding to flood disasters.